2011
DOI: 10.1111/j.1553-2712.2011.01094.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Performance of Cranial Computed Tomography Rules in Patients With Minor Head Injury: A Multicenter Prospective Study

Abstract: Objectives: The objective was to compare the predictive performance of three previously derived cranial computed tomography (CT) rules, the Canadian CT Head Rule (CCHR), the New Orleans Criteria (NOC), and National Emergency X-Ray Utilization Study (NEXUS)-II, for detecting clinically important traumatic brain injury (TBI) and the need for neurosurgical intervention in patients with blunt head trauma.Methods: This was a prospective, multicenter, observational cohort study of patients with blunt head trauma fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 18 publications
5
46
2
1
Order By: Relevance
“…When rules such as the New Orleans Criteria (NOC), Canadian CT Head Rule (CCHR), or National Emergency X-Ray Utilization Study (NEXUS-II) are used to select patients for NCCT, the sensitivity of NCCT to detect brain injuries requiring neurosurgical intervention is considered to be almost 100% [84] (evidence level Ib). A prospective study in 2,152 patients with mild TBI reported that NCCT has a very high negative predictive value (99.7%) for excluding significant intracranial injury; thus, patients can be safely discharged home without admission in the absence of other significant extracranial injuries or neurologic symptoms (evidence level Ib) [85].…”
Section: Ctmentioning
confidence: 99%
“…When rules such as the New Orleans Criteria (NOC), Canadian CT Head Rule (CCHR), or National Emergency X-Ray Utilization Study (NEXUS-II) are used to select patients for NCCT, the sensitivity of NCCT to detect brain injuries requiring neurosurgical intervention is considered to be almost 100% [84] (evidence level Ib). A prospective study in 2,152 patients with mild TBI reported that NCCT has a very high negative predictive value (99.7%) for excluding significant intracranial injury; thus, patients can be safely discharged home without admission in the absence of other significant extracranial injuries or neurologic symptoms (evidence level Ib) [85].…”
Section: Ctmentioning
confidence: 99%
“…Some studies demonstrated that the NOC is more sensitive than the CCHR in predicting clinically important brain injury, 7,11,12 whilst some studies demonstrated that the CCHR is more sensitive. 8 Some demonstrated equal sensitivity of both clinical rules in predicting clinically important brain injury.…”
Section: -14mentioning
confidence: 99%
“…Using studies from emergency/trauma literature can aid in determining the need for further imaging. Several clinical decision rules (Canadian CT Rules, New Orleans Criteria and National Emergency X-Radiography Utilization Study (Nexus II)) have been developed by studying emergency room patients [24,25]. These rules in general apply only to those patients >16 years old.…”
Section: Head and Neckmentioning
confidence: 99%
“…Athletes with worsening clinical symptoms should also be considered [23]. Although likely not as common in most sideline evaluations anticoagulation and age >65 should also prompt consideration [24,25].There is little data on length of loss of consciousness as a need for imaging. In contrast to the adult decision rules the pediatric rules use loss of consciousness, varying from suspected to greater than 5 minutes, as a variable [24, 25, 26•].…”
Section: Head and Neckmentioning
confidence: 99%